Handbook of research on design, control, and modeling of swarm robotics - Tan, Ying 1964- (Advances in computational intelligence and robotics (ACIR) book series, 2016)
"This book is a collection of the most important research achievements in swarm robotics thus far, covering the growing areas of design, control, and modeling of swarm robotics" -- Provided by publisher.